A Ru(II)-Strained Complex with 2,9-Diphenyl-1,10-phenanthroline Ligand Induces Selective Photoactivatable Chemotherapeutic Activity on Human Alveolar Carcinoma Cells via Apoptosis - Najwa Mansour; Stephanie Mehanna; Kikki Bodman-Smith; Costantine F. Daher; Rony S. Khnayzer (MDPI AG, 2023)
[Ru(bipy)2(dpphen)]Cl2 (where bipy = 2,2'-bipyridine and dpphen = 2,9-diphenyl-1,10-phenanthroline) (complex 1) is a sterically strained compound that exhibits promising in vitro photocytotoxicity on an array of cell lines. Since lung adenocarcinoma cancer remains the most common lung cancer and the leading cause of cancer deaths, the current study aims to evaluate the plausible effect and uptake of complex 1 on human alveolar carcinoma cells (A549) and mesenchymal stem cells (MSC), and assess its cytotoxicity in vitro while considering its effect on cell morphology, membrane integrity and DNA damage. MSC and A549 cells showed similar rates of complex 1 uptake with a plateau at 12 h. Upon photoactivation, complex 1 exhibited selective, potent anticancer activity against A549 cells with phototoxicity index (PI) values of 16, 25 and 39 at 24, 48 and 72 h, respectively. This effect was accompanied by a significant increase in A549-cell rounding and detachment, loss of membrane integrity and DNA damage. Flow cytometry experiments confirmed that A549 cells undergo apoptosis when treated with complex 1 followed by photoactivation. In conclusion, this present study suggests that complex 1 might be a promising candidate for photochemotherapy with photoproducts that possess selective anticancer effects in vitro. These results are encouraging to probe the potential activity of this complex in vivo.